Answer:
g(-2)= -19
g(0)= -5
g(3)= -14
Step-by-step explanation:
To find the value of f(3) we need to follow the below steps :
Step 1 : First plot the graph of f(x)
Step 2 : We need to find f(3) or the function value at x = 3 therefore, in the graph locate the point (3,0)
Step 3 : Draw a line parallel to Y-axis passing through the point (3,0) .
Step 4 : Now there exists two cases :
If the drawn line do not intersect the graph of f(x), then no value of f(3) exists for the given function of x
If the drawn line intersects the graph, then the intersection point is marked and a line parallel to x - axis is drawn passing through that marked or intersection point. And the line where it intersects the y - axis is our required value of f(3).
If this is wrong than I guess I wasn't smart enough :)
6n+1 = 25
subtract 1 from each side
6n+1-1 = 25-1
6n = 24
divide each side by 6
6n/6 = 24/6
n =4
Answer:
5713 - 75
= 5638
Step-by-step explanation:
brainliest plz
Answer:
- 5x - 3y = 9 (Example)
- y = 1/2x - 3 (Non-Example)
- 2x + 3y = 0 (Example)
- x + y = 1 (Example)
- x = 6y (Non-Example)
- y = x - 2 (Non-example)
Step-by-step explanation:
Standard form of the equation is given by:
Ax + By = C
Where
- A, B and C are constants which must be Integers. A should always be positive.
Considering the definition, we can identify the examples and non-examples of standard from of a linear equation.
<h3>
5x - 3y = 9</h3>
- In a form of Ax + By = C
- A,B and C are constants
- A=5 is positive
It is an EXAMPLE of standard form of linear function
<h3>
</h3><h3>
y = 1/2x - 3</h3>
- Not in the form of Ax + By =C
NON-EXAMPLE
<h3>
</h3><h3>
2x + 3y = 0</h3>
- In a form of Ax + By = C
- A,B and C are constants
- A=5 is positive
It is an EXAMPLE of standard form of linear function
<h3>
</h3><h3>
x + y = 1</h3>
- In a form of Ax + By = C
- A,B and C are constants
- A=5 is positive
It is an EXAMPLE of standard form of linear function
<h3>
</h3><h3>
x = 6y</h3>
- Not in the form of Ax + By =C
NON-EXAMPLE
<h3>
</h3><h3>
y = x - 2</h3>
- Not in the form of Ax + By =C
NON-EXAMPLE